Survival trends over 20 years in patients with advanced cholangiocarcinoma: Results from a national retrospective analysis of 922 cases in Italy - Casadei-Gardini, Andrea; Leone, Francesco; Brandi, Giovanni; Scartozzi, Mario; Silvestris, Nicola; Santini, Daniele; Faloppi, Luca; Aglietta, Massimo; Satolli, Maria Antonietta; Rizzo, Alessandro; Lonardi, Sara; Aprile, Giuseppe; et al. (Frontiers in Oncology, 2023)
Cholangiocarcinoma is a rare group of tumors that involve the hepatic biliary tree. Prognosis for patients with cholangiocarcinoma remains dismal. Herein, we present survival trends over a long time period spanning almost 20 years in patients with advanced cholangiocarcinoma receiving systemic chemotherapy. We retrospectively analyzed a large multicenter dataset of cholangiocarcinoma outpatients evaluated in 14 centers within the Cholangiocarcinoma Italian Group Onlus (Gruppo Italiano Colangiocarcinoma Onlus, G.I.C.O.) between 2000 and 2017 (first-line), and 2002 and 2017 (second-line). Three time periods were considered: 2000-2009, 2010-2013, and 2014-2017. A total of 922 patients (51.19% male) with cholangiocarcinoma undergoing first-line therapy were evaluated. The median durations of follow-up for progression-free survival (PFS) and overall survival (OS) were 37 and 57 months, respectively. PFS at 12 months in the three periods of starting first-line therapy was similar, ranging from 11.71% to 15.25%. OS at 12 months progressively improved (38.30%, 44.61% and 49.52%, respectively), although the differences were not statistically significant after adjusting for age, disease status, and primary tumor site. A total of 410 patients (48.5% male) underwent second-line chemotherapy. The median durations of follow-up for PFS and OS were 47.6 and 41.90 months, respectively. An OS of 24.3%, 32.3%, and 33.1% was observed in 2002-2009, 2010-2013, and 2014-2017, respectively. Despite incremental benefits across years, our clinical experience confirms that modest overall advances have been achieved with first- and second-line chemotherapy in advanced cholangiocarcinoma. Efforts should focus on the identification of patients who derive the greatest benefit from treatment.